Determination of the degree of contamination of shellfish by copper Niger Enoplochiton Bay Huarmey - Cabrera Carranza, Carlos Francisco (2012)
In order to evaluate the copper content in the mollusc existing Enoplochiton Niger Huarmey Bay in the province of Huarmey, department of Ancash, Peru, the concentration (ug / g) of copper in the muscle of the mollusk was determined by the technique atomic absorption spectrophotometry in the laboratory that used CERPER Method: NOM-117-SSA 1-1994. The samples were homogenized and subjected to wet digestion. To collect samples of shellfish was necessary to establish thirteen sampling stations along Huarmey Bay Area. Seven of these stations were located north of Puerto Punta Lobitos six were located to the south. The year 2001 in Puerto Punta Lobitos occurred an accidental spill of copper concentrate into the sea. Analysis of variance was performed to compare the weight data of copper in relation to the size of the mollusk (II size> 40 mm and ≤ 40 mm Size I) and in relation to the distance to Puerto Punta Lobitos. The copper concentration in the muscle of the mollusc was 0.132 ± 1.648 mg / g for the size II and 1.395 ± 0.075 mg / g for the size I. This particular concentration does not exceed the Maximum Permissible Limit for International Copper molluscs which is 30 ug / g. The highest concentration of copper was 1.82 mg / g in Punta Boqueron. The copper concentration in the muscle of the mollusk has an inverse correlation to the distance to Puerto Punta Lobitos. Copper concentration was compared according to the size of the mollusk in one sampling station.